Discovery of Diaryl Ether Substituted Tetrahydrophthalazinones as TbrPDEB1 Inhibitors Following Structure-Based Virtual Screening - de Heuvel, Erik; Kooistra, Albert J.; Edink, Ewald; van Klaveren, Sjors; Stuijt, Jeffrey; van der Meer, Tiffany; Sadek, Payman; Mabille, Dorien; Caljon, Guy; Maes, Louis; Siderius, Marco; de Esch, Iwan J. P.; et al. (Frontiers in Chemistry, 2021)
Several 3′,5′-cyclic nucleotide phosphodiesterases (PDEs) are validated drug targets for a large variety of diseases. The parasitic protozoan Trypanosoma brucei, causative agent of human African trypanosomiasis, contains several cyclic AMP specific PDEs from which TbrPDEB1 is validated as a drug target. The recent discovery of selective TbrPDEB1 inhibitors has increased their potential for a novel treatment for this disease. Compounds characterized by a rigid biphenyl tetrahydrophthalazinone core structure were used as starting point for the exploration of novel TbrPDEB1 inhibitors. Using a virtual screening campaign and structure-guided design, diaryl ether substituted phthalazinones were identified as novel TbrPDEB1 inhibitors with IC50 values around 1 µM against Trypanosoma brucei. This study provides important SAR information for the future design of effective parasite-specific PDE inhibitors.